Perubahan Semantik Kosakata Serapan Bahasa Asing dalam Bahasa Indonesia - Nadya Fitri Lestari; Mohd. Harun; Siti Sarah (Phonologie : Journal of Language and Literature, 2021)
Abstract. This study aims to describe the changes in meaning that occur in foreign language absorption vocabulary in Indonesian. The data source in this study is Indonesian vocabulary absorbed from Foreign languages, namely Dutch and English. The data in this study is a dictionary of foreign absorption words in Indonesian by J.S Badudu. Data collection techniques using document review techniques. This research uses qualitative approach and research type using descriptive method. The results of this study researchers found the words absorption that experienced a change in meaning, as for the word absorption that experienced changes in meaning in the form of expansion, narrowing and total changes. The expansion of meaning is a process that occurs in a word that at first only has a meaning, but then because various factors become have other meanings. The Dutch example of the word "paniek" means panic. The narrowing of meaning is a process that occurs in a word that initially has a broad enough meaning, then changes to be limited to a meaning only. Examples of such emphasis words in English are pressure and heavy points, while the meaning in Indonesian is the pressure on syllables or on words and the emphasis on importance (something). The total change of meaning is a process of changing the meaning that has now been much different from the meaning of the original word. Examples of the word "morgem (BB)" are absorbed in The Indonesian language into besuk. The change in meaning that occurs because of the shift in meaning is the word besuk means making a visit to the hospital to visit people who are sick